Attitudes toward English: a Hungarian Minority Context in Vojvodina, Serbia - Halupka-Rešetar, Sabina J.; Kovač Rac, Eleonora J. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Although there is abundant literature on attitudes toward English, much less has so far been said about the attitudes of minority language speakers toward a foreign language, especially in contexts in which the minority language speakers receive formal education in their L1 and are not immersed in an English environment. The paper presents the results of a survey conducted among grammar schools pupils in Vojvodina (Serbia) whose L1 is Hungarian and who have been studying English for over 10 years. There were two groups of research participants, based on the area where they live (compact vs diffuse language community). The research instrument was a questionnaire, which contained two parts: the first part investigated the participants’ profile and the second part explored the participants’ value judgements regarding English. The results of the study confirm the initial hypothesis that students living in a diffuse environment will be open to exposure to English and that their attitudes to EFL will be more positive than the attitudes of students living in a compact environment. Only some of the more general independent variables included in the study show an interaction with positive attitudes towards English. The results of the study lead to pinpointing some determinants of the attitudes Hungarian L1 students in Serbia hold toward English, thereby adding to the scarce literature on minority speakers’ attitudes to a foreign language in a multilingual and multicultural area like Vojvodina.